Analisis Kinerja Turbin Francis Horizontal Terhadap Variasi Debit Pada Sistem Pltmh Aek Sigeaon (The Performance Analysis Of Horizontal Francis Turbine To Discharge Variations In The Aek Sigeaon Micro Power Plant System: Analisis Kinerja Turbin Francis Horizontal Terhadap Variasi Debit Pada Sistem Pltmh Aek Sigeaon (The Performance Analysis Of Horizontal Francis Turbine To Discharge Variations In The Aek Sigeaon Micro Power Plant System - puspawan angky; Hotmariana R Hutasoit; Nurul Iman Supardi; Jodi Trinaldi Manalu (UNIB Press, 2025)
Micro hydro power plant (PLTMH) is a small-scale power plant that uses water in small discharges as its driving source. Water that can be utilized in PLTMH technology can come from irrigation channels, rivers or natural waterfalls. In general, PLTMH has three main components, namely water, water turbines, and generators. The purpose of this study is to analyze the effect of variations in water discharge on the performance of horizontal francis turbines in the Aek Sigeaon Micro Hydro Power Plant (PLTMH) system. The main focus of this study is to observe changes in input power, output power, and turbine efficiency as a result of variations in water discharge that occur in the field. Data collection was carried out using a SCADA monitoring system to obtain operational parameters in real time such as water discharge, pressure, current, and voltage. The results showed that an increase in water discharge generally caused an increase in input and output power, but was not always directly proportional to turbine efficiency. The highest turbine efficiency of 77.8% was obtained at a water discharge of 3.48 m³/s, while the lowest efficiency of 54.65% occurred at a water discharge of 6.01 m³/s. This shows that the horizontal Francis turbine works more efficiently at low to medium discharge.